Perancangan Sistem Greenhouse Cerdas Berbasis Internet of Things (IoT) dengan Penyiraman Otomatis dan Monitoring Berbasis Web menggunakan ESP32 - Pradipta Aryasetya; Rizky Eka Adinagoro; Pramono Pramono (Jurnal Kendali Teknik dan Sains, 2026)
This study presents a design for an IoT-based smart greenhouse system with automatic watering and web-based monitoring using the ESP32 microcontroller. The main issue addressed is manual plant watering that makes it difficult for users to monitor soil moisture, temperature, air humidity, and irrigation efficiency in real time. The system is designed using capacitive soil moisture sensors, DHT11, 1-channel relays, 12 V DC pump, and a web dashboard application based on React with chart.js for remote monitoring and control. The method used is Research and Development (R&D) with a prototyping approach, as the study focuses on designing, building, integrating, and testing IoT devices through iterative stages. Sensor data is transmitted to a Node.js backend server in the form of percentages and plant condition status, while the pump can be controlled via the web dashboard or hysteresis-based automatic mode (35-45% soil moisture). The system is equipped with a 120-item local buffer for offline resilience and automatic database archiving every hour for data storage efficiency. Intelligent irrigation algorithms use VPD (Vapor Pressure Deficit) computation and trend analysis to provide optimal watering recommendations. The system has been designed with a modular architecture that allows scalability and integration of additional sensors.